Comunicación interna y satisfacción laboral de los colaboradores del área de recaudación de Electro Oriente Iquitos 2024 - Armas Flores, Renzo Alejandro (2024)
The determination of this study was the relationship between the variables within the collaborators of the collection area of Electro Oriente, Iquitos 2024; Likewise, an experimental design was not used, but it did have a quantitative approach, with a cross-sectional and correlational methodology, to observe and analyze how these variables are related at a specific time without manipulating them. The results revealed a Pearson correlation (0.948) with bilateral significance of 0.000, indicating a statistically significant and positive relationship between the variables. This means that improvements in internal communication are associated with an increase in employee job satisfaction. The conclusions highlight that internal communication has a significant impact on job satisfaction, with a high correlation value that reinforces the proposed hypothesis. The findings are relevant since they strongly highlight what was mentioned above.